Construction of Environmental DNA Libraries in Escherichia coli and Screening for the Presence of Genes Conferring Utilization of 4-Hydroxybutyrate - Henne, Anke (American Society for Microbiology, 1999)
Environmental DNA libraries from three different soil samples were constructed. The average insert size was 5 to 8 kb and the percentage of plasmids with inserts was approximately 80%. The recombinant Escherichia coli strains (approximately 930,000) were screened for 4-hydroxybutyrate utilization. Thirty-six positive E. coli clones were obtained during the initial screen, and five of them contained a recombinant plasmid (pAH1 to pAH5) which conferred a stable 4-hydroxybutyrate-positive phenotype. These E. coli clones were studied further. All five were able to grow with 4-hydroxybutyrate as sole carbon and energy source and exhibited 4-hydroxybutyrate dehydrogenase activity in crude extracts. Sequencing of pAH5 revealed a gene homologous to the gbd gene of Ralstonia eutropha, which encodes a 4-hydroxybutyrate dehydrogenase. Two other genes (orf1 and orf6) conferring utilization of 4-hydroxybutyrate were identified during subcloning and sequencing of the inserts of pAH1 and pAH3. The deduced orf1 gene product showed similarities to members of the DedA family of proteins. The sequence of the deduced orf6 gene product harbors the fingerprint pattern of enoyl-coenzyme A hydratases/isomerases. The other sequenced inserts of the plasmids recovered from the positive clones revealed no significant similarity to any other gene or gene product whose sequence is available in the National Center for Biotechnology Information databases.